Laser Spectroscopy 2: Experimental Techniques - Demtröder, Wolfgang (Springer, 2015)
Keeping abreast of the latest techniques and applications, this new edition of the standard reference and graduate text on laser spectroscopy has been completely revised and expanded. While the general concept is unchanged, the new edition features a broad array of new material, e.g., ultrafast lasers (atto- and femto-second lasers), coherent matter waves, Doppler-free Fourier spectroscopy, interference spectroscopy, quantum optics and gravitational waves and still more applications in chemical analysis, medical diagnostics, and engineering.